ASSESSMENT OF COLLABORATIVE SKILLS - Piniuta, Irina (Proceedings of National Aviation University (archive), 2019)
The article deals with the assessment of the ways to develop collaborative skills. In the study, the students were suggested to do activities in teams using traditional practices and by means of Google Docs and Meeting Words web applications. Using the criteria of equality, participation and shareness the development of collaborative skills was assessed. The mixed research method which combined the survey of the students and the content analysis of students’ projects helped to reveal the effectiveness of using technology in the development of collaborative skills.